Konstruksi Yuridis terhadap Pertimbangan Majelis Hakim dalam Putusan Nomor 46/Pid.Sus/2021/Pn.Srg berdasarkan Peraturan Perundang –Undangan - Sahri , Fidri; Juanda, Juanda (Jurnal Ilmu Multidisiplin, 2023)
The crime of money laundering (TPPU) does not stand alone because the assets that are placed, transferred, or diverted by means of integration are obtained from criminal acts, with other criminal acts that precede it (predicate crime). There are twenty-six types of predicate crimes obtained from the proceeds of TPPU assets as stipulated in Article 2 Paragraph (1) of Law No. 8 of 2010. Basically these activities consist of three steps which each stand alone but are often carried out together as contained in the case with Decision Number 46/Pid.Sus/2021/Pn. Srg. This study uses a normative juridical research method using a statutory approach. Based on the results of the research, it can be seen that the juridical construction is considered by the judge in deciding case number 46/Pid.Sus/2021/Pn. Srg. When viewed based on legal principles, the application of these articles is appropriate for the criminal acts committed by the defendants, but based on the principle of justice, the decisions issued by the Panel of Judges are deemed unable to fulfill a sense of justice.